2020
DOI: 10.1002/evl3.169
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of ancient admixture to reproductive isolation between European sea bass lineages

Abstract: Understanding how new species arise through the progressive establishment of reproductive isolation (RI) barriers between diverging populations is a major goal in Evolutionary Biology. An important result of speciation genomics studies is that genomic regions involved in RI frequently harbor anciently diverged haplotypes that predate the reconstructed history of species divergence. The possible origins of these old alleles remain much debated, as they relate to contrasting mechanisms of speciation that are not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 90 publications
(179 reference statements)
6
30
0
Order By: Relevance
“…In addition, many models make an implicit assumption that two allopatric lineages only differ by fixed alleles, which does not capture the empirical diversity among individuals' gene expression (Kelly et al, 2017;Tyler et al, 2017;Gould et al, 2018;Mogil et al, 2018;Ryu et al, 2019) nor the observed importance of regulatory disruption and standing genetic variation in generating reproductive isolation (Hopkins and Rausher, 2011;Wittkopp and Kalay, 2012;Guerrero et al, 2016;Rougeux et al, 2019;Morgan et al, 2020). More importantly, substitutions originating from de-novo mutations fail to explain the recent evidence that alleles underlying reproductive barriers often predate speciation events and can evolve along parallel evolutionary trajectories (Kaeuffer et al, 2012;Sicard et al, 2015;Meier et al, 2017;Nelson and Cresko, 2018;Wang et al, 2019;Duranton et al, 2019;Marques et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many models make an implicit assumption that two allopatric lineages only differ by fixed alleles, which does not capture the empirical diversity among individuals' gene expression (Kelly et al, 2017;Tyler et al, 2017;Gould et al, 2018;Mogil et al, 2018;Ryu et al, 2019) nor the observed importance of regulatory disruption and standing genetic variation in generating reproductive isolation (Hopkins and Rausher, 2011;Wittkopp and Kalay, 2012;Guerrero et al, 2016;Rougeux et al, 2019;Morgan et al, 2020). More importantly, substitutions originating from de-novo mutations fail to explain the recent evidence that alleles underlying reproductive barriers often predate speciation events and can evolve along parallel evolutionary trajectories (Kaeuffer et al, 2012;Sicard et al, 2015;Meier et al, 2017;Nelson and Cresko, 2018;Wang et al, 2019;Duranton et al, 2019;Marques et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation between the populations has been widely reported at the genomic level (Duranton et al, 2018) and associated with phenotypic variation in sex ratio, muscle fat or resistance to viral nervous necrosis (Doan et al, 2017;Guinand et al, 2017). Duranton et al (2020) demonstrated that the maintenance of the genomic differentiation between the AT and Mediterranean populations was due to reproductive isolation barriers established after the ancient admixture of the Atlantic European sea bass with the closely related Dicentrarchus punctatus. In addition, the subsequent rapid fixation of some D. punctatus alleles in the Atlantic D. labrax could have provided a selective advantage in the Atlantic environment compared to ancestral D. labrax alleles (Duranton et al, 2020).…”
Section: Variability Between Temperatures and Populationsmentioning
confidence: 98%
“…Duranton et al (2020) demonstrated that the maintenance of the genomic differentiation between the AT and Mediterranean populations was due to reproductive isolation barriers established after the ancient admixture of the Atlantic European sea bass with the closely related Dicentrarchus punctatus. In addition, the subsequent rapid fixation of some D. punctatus alleles in the Atlantic D. labrax could have provided a selective advantage in the Atlantic environment compared to ancestral D. labrax alleles (Duranton et al, 2020). Results from the six different feeding rates (from 100% ADL to 0% ADL) showed that for an equal value of StdFI, fish from the EM population and fish reared at 18 • C had the highest StdBWG, and thus were the most efficient.…”
Section: Variability Between Temperatures and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local ancestry tracts provide the most direct evidence for hybridisation, as they cannot be explained by incomplete lineage sorting or convergence (Rieseberg et al 2000). They have been used to infer the number of generations required to stabilise a hybrid sunflower species (Ungerer et al 1998), uncover the lack of F2 or deeper hybrid generations in a Populus hybrid zone (Christe et al 2016), compare the age of two separate hybrid zones of Lissotriton newts (Zieliński et al 2019), detect past episodes of hybridisation (Meier et al 2017;Węcek et al 2017;Duranton et al 2020), localise introgressed genomic segments (Huerta-Sánchez et al 2014;vonHoldt et al 2016), identify incompatible haplotype combinations in hybrid swordfish (Powell et al 2020), and monitor shifts in genome composition in experimental Drosophila populations (Matute et al 2020). The rapidly growing theoretical literature infers evolutionary processes from genome-wide local ancestry patterns, from the age of ancient admixture pulses (Harris and Nielsen 2013) to the onset of neutral mixing with continuous gene flow (Sedghifar et al 2015), adaptive introgression (Sachdeva and Barton 2018;Shchur et al 2019), and selection against deleterious allele combinations in hybrid zones (Sedghifar et al 2016;Hvala et al 2018).…”
Section: Introductionmentioning
confidence: 99%